Flagrancia delictiva y detención arbitraria efectuado por efectivos policiales de la Comisaría de Iquitos segundo semestre 2024 - Noriega Piña, Marco Antonio (2025)
The objective was to examine the connection between flagrante delicto and arbitrary detention carried out by police officers of the Iquitos Police Station during the second semester of 2024. The study is quantitative - non-experimental correlational in a population of 70 and a sample of 32 cases of in flagrante delicto and arbitrary detention in the police station of Iquitos during the second semester of 2024. In the DESCRIPTIVE analysis of flagrante delicto in police procedures. The majority of participants considered the application of flagrancy to be “Adequate” (59.4%), followed by “Optimal” (21.9%) and “Insufficient” (18.8%). This suggests that, although more than half believe that the application of flagrancy is adequate, there is a significant proportion that perceives deficiencies, indicating the need to review or strengthen the criteria to improve the perception of its adequacy. Regarding the perception of arbitrary detention, the distribution of responses is similar. The majority rated the practice as “Adequate” (59.4%), while 21.9% rated it as “Optimal” and 18.8% rated it as “Insufficient”. This indicates that, although the majority see detentions as adequately handled, there is a considerable fraction who perceive them as potentially arbitrary, which could reflect a concern regarding the objectivity and fairness of these procedures. In the INFERENTIAL analysis: 8 boxes (88.9%) had a count less than 5, which is the most frequent occurrence. The expected value is 1.13. The normalized figure was 5,568. The value of the Chi-square statistic and the p-value less than 0.001 indicate a significant association between the variables analyzed. However, the caveat that 88.9% of the cells have expected counts less than 5 suggests that the Chi-square test may not be fully reliable in this case. The Fisher-Freeman-Halton test was performed. Statistical decision: In the chi-square test the p-value is 0.000, lower than the significance level 0.05; therefore, the Ho is rejected and the Ha is accepted: The inadequate application of the concept of flagrante delicto by the police officers of the Iquitos Police Station during the second semester of 2024 increases the probability of arbitrary detentions, affecting the fundamental rights of the detainees.